40. COMPLIANCE WITH THE USE OF VITAMIN K ANTI-COAGULANT DRUGS IN PATIENTS AFTER MECHANICAL HEART VALVE REPLACEMENT SURGERY AT THE CARDIOLOGY CLINIC, DA NANG HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: To describe medication adherence and analyze the relationship between adherence to vitamin K antagonist anticoagulant use and some factors in patients after mechanical heart valve replacement surgery at the Cardiology Clinic, Da Nang Hospital.Methods: A cross-sectional study on 277 patients after mechanical heart valve replacement who were being treated as outpatients at the Cardiovascular Surgery Clinic, Da Nang Hospital. The questionnaire consisted of 3 parts: General characteristics of the patients, anticoagulant knowledge scale (AKT), and medication adherence scale (GMAS).Results: The patient's compliance rate with anti-vitamin K anticoagulants was 91%, and non-compliance was 9%. Alcohol/beer consumption, duration of medication use, and knowledge about anti-vitamin K anticoagulants were considered factors related to patient's compliance.Conclusion: The rate of compliance with anti-vitamin K anticoagulants among patients is quite high, however, there is still a small percentage of patients who do not comply, which seriously affects the health status of patients after mechanical heart valve replacement. It is necessary to develop appropriate health education and counseling programs for patients.
Keywords: Compliance with medication use; anti-vitamin K anticoagulants; heart valve replacement